Bubbling fluidized bed biomass gasification and product gas cleaning - Ul Hai, Irfan (2017)
Biomass is used for fuel by humanity from prehistoric times. With the passage of time and to meet the energy needs, non-conventional ways of utilizing the conventional sources became an interest with use of technologies. Biomass gasification is a proven technology that can economically use alternative energy resource of “Carbon Neutral”. Biomass product gas from biomass gasification is composed of CO, CO2, CH4, H2, other hydrocarbons, traces of other components and tar from biomass gasification. Fluidized bed gasification is one of the promising technologies to achieve high thermal conversion efficiency as it takes great advantages of fluidization in terms of uniform temperature profiles and excellent gas-solid interactions. The present research is aimed to evaluate the performance of a bubbling fluidized bed biomass gasifier for product gas production composition using air as gasification agent and SRC willow chips as biomass. Particle capture efficiency of the mop fan and an effect of different operating conditions such as bed temperature, equivalent ratio on the product gas composition and heating value are also investigated at Institute of Sustainable Energy Technology, University of Nottingham. The concentrations of particulate matter in the product gas before and after the mop fan cleaning unit are measured to assess the performance of the cleaning unit. Different fan rotating speeds and different flow rates of spray water are used to optimise the particle removal efficiency of this unit. It has been found that the mop fan cleaning unit has achieved an efficiency of 90% in removing particle matters and an efficiency of more than 80% in removing N-species presented in the product gas. Tars appear as a major issue in the product gas and should be removed from the product gas before they get condensed in the equipments which utilise product gas. Tar arrest techniques were successfully tested in this investigation such as woodchips bed, water spray and mop fan. The synergic effect of tar removal of water spray and mop fan found to be more effective in removing tars as if used individually. Different spray water amounts were used with a constant fan speed for keen observation of tars’ solubility in the water and found reasonable removal of tars from product gas.